2022
DOI: 10.1108/apjml-05-2022-0385
|View full text |Cite
|
Sign up to set email alerts
|

Poison or remedy? Masculinity in a pathos-based sustainable brand story

Abstract: PurposeThis study aims to examine the effects of pathos in sustainable brand stories featuring masculinity on brand masculinity and men’s sustainable brand attitude using Aristotle’s rhetoric theory.Design/methodology/approachThree independent online experiments (N = 398; N = 216; N = 247) were conducted to observe how participants responded to a sustainable brand story. Data collected through a post-experimental survey were used to test the proposed model. Research hypotheses were inspected using SPSS.Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…They then label it competent (Fiske et al, 2007;Ren et al, 2023). Stereotypes, such as warmth and competence, play significant roles in predicting consumers' good behavior and fostering consumerbrand associations (Diamantopoulos et al, 2021;Huang et al, 2023;Japutra et al, 2020). More specifically, stereotypes allow for the evaluation of a brand's consumer-based identity (Gunturkun et al, 2020;He and Ge, 2023;Kolbl et al, 2019).…”
Section: H1mentioning
confidence: 99%
“…They then label it competent (Fiske et al, 2007;Ren et al, 2023). Stereotypes, such as warmth and competence, play significant roles in predicting consumers' good behavior and fostering consumerbrand associations (Diamantopoulos et al, 2021;Huang et al, 2023;Japutra et al, 2020). More specifically, stereotypes allow for the evaluation of a brand's consumer-based identity (Gunturkun et al, 2020;He and Ge, 2023;Kolbl et al, 2019).…”
Section: H1mentioning
confidence: 99%
“…Regarding gender stereotypes, previous research has found that green consumption is interpreted in a feminine fashion, with most consumers linking such shopping responses to femininity (Brough et al, 2016;Obermiller and Isaac, 2018). Accordingly, a relatively novel way to understand why male and female consumers are sometimes differentially inclined to engage in green consumption, beyond established sex differences in certain personality traits, is to attribute these sex-specific patterns to the green-feminine stereotype (Borau et al, 2021;Brough et al, 2016;Felix et al, 2022;Huang et al, 2022). In other words, men may be more motivated than women to actively avoid green consumption to preserve a macho image (Bloodhart and Swim, 2020;McLelland et al, 2022;Rozin et al, 2012).…”
Section: Sex Differences In Green Consumption Valuesmentioning
confidence: 99%